2020
DOI: 10.3390/genes11111357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Milk Fat Metabolism-Related Pathways of the Bovine Mammary Gland during Mid and Late Lactation and Functional Verification of the ACSL4 Gene

Abstract: The concentration of bovine milk fat changes regularly with lactation stages. In particular, milk fat percentage is higher in late lactation than mid lactation. Furthermore, milk fat composition is highly subject to a few genes. Thus, transcriptome sequencing was performed to explore the expression patterns of differentially-expressed genes (DEGs) in the parenchymal mammary gland of Holstein dairy cows between mid and late lactation. The 725 DEGs were screened (fold change > 2 and p-value < 0.05), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…It suggests that the ACSL4 could stimulate adipogenesis and is more effective in the early stage of adipogenic differentiation. Therefore, consistent with other studies, ACSL4 is a positive regulator of adipogenic differentiation of adipocytes [ 9 , 25 , 26 ], epithelial cells [ 27 ], and smooth muscle cells [ 28 ] from different tissue origins. Our data also showed that ACSL4 expression remains low in the matured adipocytes, indicating that ACSL4 is dispensable for the maintenance of fat cells and lipid storage.…”
Section: Discussionsupporting
confidence: 91%
“…It suggests that the ACSL4 could stimulate adipogenesis and is more effective in the early stage of adipogenic differentiation. Therefore, consistent with other studies, ACSL4 is a positive regulator of adipogenic differentiation of adipocytes [ 9 , 25 , 26 ], epithelial cells [ 27 ], and smooth muscle cells [ 28 ] from different tissue origins. Our data also showed that ACSL4 expression remains low in the matured adipocytes, indicating that ACSL4 is dispensable for the maintenance of fat cells and lipid storage.…”
Section: Discussionsupporting
confidence: 91%
“…PPARγ expression increases during changes in the lactation period [55,56], thereby regulating peroxisomal β-oxidation to prevent metabolic stress. Research further confirmed the importance of PPARγ in regulating milk fat production [57,58]. Similarly, as milk-producing ruminants, goats and sheep are also regulated by PPARγ.…”
Section: Pparγmentioning
confidence: 73%
“…Present studies have demonstrated that the ACSL4 dysregulation is associated with the progression of many malignant tumors, including gastric cancer, prostate cancer, and colorectal cancer ( 57 – 59 ). What’s more, ACSL4 could regulate lipogenesis by affecting the expression of FASN and ACC1 ( 60 , 61 ). Therefore, we speculated that lncRNATSPEAR-AS2 could affect fatty acid metabolism of CRC through the targeted regulation of ACSL4, which still needs further experiments to prove.…”
Section: Discussionmentioning
confidence: 99%